AN ANALYSIS OF FIGURATIVE LANGUAGE USED IN POEM OF THE ECHOING GREEN BY WILLIAM BLAKE - Muji Endah Palupi (STIBA IEC JAKARTA, 2021)
The purpose of this research is to study an analysis of figurative language in poetry. People are interested in reading literary books because reading literary books makes them to understand about life, human and nature. Reading literary books can get pleasure. The language used in poetry make more complex. Figurative language can make create interesting poetry. It is important to know the meaning of poems. Sometimes people read poetry without understanding the meaning conveyed. Poetry is a collection of words that express emotions or ideas into a literary text. In poetry there are many elements of language. English poetry can help students to improve their vocabulary skills. Poetry improves skills in listening word for word conveyed from the reader of the poem. Poetry analysis examines the elements of language to understand literary works as a whole. Analyzing a poem line by line allows you to learn about its structure, form, language, metric patterns, and themes. Hopefully this research can be widely accepted so that readers will be interested in knowing more about poetry and it is nuances